The Transcriptional and Splicing Changes Caused by Hybridization Can Be Globally Recovered by Genome Doubling during Allopolyploidization. (15th February 2021) - Qin, Jinxia; Mo, Ruirui; Li, Hongxia; Ni, Zhongfu; Sun, Qixin; Liu, Zhenshan
Abstract: Polyploidization is a major driving force in plant evolution. Allopolyploidization, involving hybridization and genome doubling, can cause extensive transcriptome reprogramming which confers allopolyploids higher evolutionary potential than their diploid progenitors. To date, little is known about the interplay between hybridization and genome doubling in transcriptome reprogramming. Here, we performed genome-wide analyses of transcriptome reprogramming during allopolyploidization in wheat and brassica lineages. Our results indicated that hybridization-induced transcriptional and splicing changes of genes can be largely recovered to parental levels by genome doubling in allopolyploids. As transcriptome reprogramming is an important contributor to heterosis, our finding updates a longstanding theory that heterosis in interspecific hybrids can be permanently fixed through genome doubling. Our results also indicated that much of the transcriptome reprogramming in interspecific hybrids was not caused by the merging of two parental genomes, providing novel insights into the mechanisms underlying both heterosis and hybrid speciation.